SYNTHESIS OF NEW SCHIFF BASES OF GOSSYPOL WITH BENZIDINE (Scientific journal of the Fergana State University, 2022)
This article describes the synthesis of new Schiff bases of the gossypol substance, isolated from common cotton in our republic, with benzidine in various ratios, the study of some physicochemical properties of the new synthesized compounds, the preparation of metal complexes of the obtained Schiff bases with some bulk metals and methods for controlling their properties.